Ekstrak Etanol dan Fraksi Heksan Buah Pare (Momordica charantia) Sebagai Penurun Kadar Glukosa Darah Tikus Diabetes (ETHANOL EXTRACT AND HEXANE FRACTION OF MOMORDICA CHARANTIA DECREASE BLOOD GLUCOSE LEVEL OF DIABETIC RAT) - Suartha, I Nyoman; Swantara, I Made Dira; Rita, Wiwik Susanah (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
The research on the potency of Momordica charantia as lowering blood glucose has been carried out.The fruit was extracted by 70 % ethanol at room temperature. The extract was then partition with NHexane.The filtrate of partition was purified with thin layer chromatography. Three months old of whitemale rats (Rattus novergicus) with approximately 200-250 grams in weight were used as Bio-indicators.This study used a randomized block design (CRD) consisting of eight treatment groups (each treatmentconsisted of five rats). Rats were injected with streptozotocin to get hyperglycemic condition. The M.charantia fruit fraction (fraction 1-5) with dose 100 mg/kg bw was treated to each group when the ratt wason hyperglycemic condition. Rat blood glucose levels were observed on days 0, 4, 11, and 18 respectively .The results showed that blood glucose levels of M. charantia fraction 1and 5 with dose of 100 mg/kg bwhave the same effect with a negative control from day 4th, fraction 2 on day 18 whereas The others fractionare 3, and 4 were effect on days 18th. Based on the result it can be concluded that the M. charantia fraction1 with dose of 100 mg/kg bw effectively in decreasing the blood glucose levels of diabetic rat.
Keywords: blood glucose, M. charantia, chromatography